2020
DOI: 10.1093/femsyr/foaa016
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Mycocins: a great potential for application in health

Abstract: Mycocins have demonstrated inhibition of fungi, bacteria, parasites and viruses, in addition to being studied as epidemiological markers and in the development of vaccines. They are defined as extracellular proteins or glycoproteins with different activities, the main mechanism of action being the inhibition of β-glucan synthesis in the cell wall of sensitive strains. Given the resistance problems created by several microorganisms to agents commonly used in clinical practice, the discovery of new substances wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
8
0
2
Order By: Relevance
“…Also, mycocins interfere with the synthesis of genetic material and consequently with cell division, producing the known killer phenomenon. 41,42 Banjara et al (2016) 41 observed the production of mycocins by DH strains which were able to inhibit Candida albicans and C. tropicalis yeasts, especially under pH conditions from 4.5 to 5.5 and temperatures from 25°C to 30°C. 41 In addition, Chen et al (2015) 43 studied the production of mycocins by KM at pH 2 and 8, and the inhibitory effect on Escherichia coli was mainly observed in a temperature range from 25°C to 45°C.…”
Section: Whey Fermentation Under Monoculture Modementioning
confidence: 99%
“…Also, mycocins interfere with the synthesis of genetic material and consequently with cell division, producing the known killer phenomenon. 41,42 Banjara et al (2016) 41 observed the production of mycocins by DH strains which were able to inhibit Candida albicans and C. tropicalis yeasts, especially under pH conditions from 4.5 to 5.5 and temperatures from 25°C to 30°C. 41 In addition, Chen et al (2015) 43 studied the production of mycocins by KM at pH 2 and 8, and the inhibitory effect on Escherichia coli was mainly observed in a temperature range from 25°C to 45°C.…”
Section: Whey Fermentation Under Monoculture Modementioning
confidence: 99%
“…Some authors conclude the mycocins can be are studied as new molecules and potential candidates to develop new antifungal due to their broad spectrum of action (Aloui et al, 2015;Paris et al, 2016). Nascimento et al, (2020) reported that mycocins have an antimicrobial action, and are minimally toxic to human cells. Junges et al (2020) confirmed this low toxicity of mycocins, by the cytotoxicity tests in Artemia salina Leach.…”
Section: Introductionmentioning
confidence: 99%
“…O pH inicial do gel T1 foi de 5.8, o gel T2 apresentou pH 5.7, enquanto o gel C+ e Capresentaram ambos pH de 6.0. Isso se deve ao fato de que as micocinas possuem característica ácida, aproximadamente pH 4.7 [15,24,53] e sua incorporação desencadeou uma pequena variação de pH na formulação quando comparada aos controles (Figura 3). Durante este estudo, o pH evidenciou variações mínimas de acordo com o esperado.…”
Section: Ciclo Gelo/degelounclassified
“…No que se refere à aplicação industrial, a levedura W. anomalus possui vasto potencial biotecnológico entre a indústria; em fermentações, é utilizada como biocontrole por competição com leveduras e fungos indesejáveis, sendo essa sua aplicação mais estudada [12,22]. Assim, as micocinas produzidas por W. anomalus são consideradas substâncias naturais de baixa toxicidade em células humanas, sendo fortes candidatas ao desenvolvimento de novos antimicrobianos com grande potencial de aplicação e interesse para a indústria farmacêutica [15,23,24].…”
Section: Introductionunclassified